(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article examines the issues of improving the organizational and economic mechanisms of managing the activities of industrial enterprises in Uzbekistan, particularly, in the case of agricultural production enterprises. Agricultural enterprises play an important role in the economy of Uzbekistan and are of great importance in ensuring the country’s food security, as well as in increasing the export potential. At the same time, there are several problems in the effective management of the activities of these enterprises: problems such as underdeveloped infrastructure, lack of financial resources, and lack of qualified personnel need to be solved. In the article, the essence, tasks and methods of improving the organizational and economic mechanisms in the management of enterprises are extensively analyzed. Special attention is paid to modern methods and approaches of enterprise management, as well as infrastructure development, introduction of innovations, financial support and personnel training. Through these improvement measures, it is possible to increase the efficiency of agricultural production enterprises, ensure food security and achieve economic growth.